2022
DOI: 10.4081/ijfs.2022.10051
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of food safety knowledge, attitude, practices of food handlers and microbial contamination in foods at the canteens of a University in Pakistan

Abstract: Developing nations are striving to assure food safety that rely mainly upon handling procedures. The current study focused upon the understanding level and practices of food handlers working at various canteens of University of the Punjab, Quid-i-Azam campus, Lahore. Different canteens were selected where 300 different food handlers were judged for their approach towards food safety through a closed ended questionnaire. Samples of different food products were also taken randomly for their microbiological safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
2
1
1
Order By: Relevance
“…Similar findings have been discovered in prior studies [ 9 , 39 ]. However, the findings differed from those of a Pakistan-based study [ 7 ]. For example, 25% of 300 food handlers at the University of Punjab's various canteens still do not use soap when washing their hands, and 55.9% do not wear proper uniforms while on the job.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar findings have been discovered in prior studies [ 9 , 39 ]. However, the findings differed from those of a Pakistan-based study [ 7 ]. For example, 25% of 300 food handlers at the University of Punjab's various canteens still do not use soap when washing their hands, and 55.9% do not wear proper uniforms while on the job.…”
Section: Discussioncontrasting
confidence: 99%
“…This study reported that workers had moderate knowledge (59.7%) and practice (50%), which is slightly lower than the findings of the current study [ 22 ]. The findings are in line with earlier research in Pakistan (60.0% knowledge and 58.0% practice) [ 7 ], Malaysia (61.7% knowledge and 53.2% practice) [ 37 ], Lebanon (59.2% knowledge and 83.2% practice) (although practice score was higher) [ 9 ], and lower than Sudan (70.1% knowledge and 74.4% practice) [ 38 ]. The discrepancies reported among studies may be ascribed to disparities in study design, study sites, cutoff thresholds, training, and the accessibility of information pertaining to food hygiene and safety.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Sikap yang tepat dari pekerja dapat mengurangi wabah yang ditularkan melalui pangan. Penularan mikroben patogen dapat dikurangi dengan menerapkan prinsip higiene yang baik dan penanganan pangan yang benar (Ali et al 2022).…”
Section: Pendahuluanunclassified